Both F-18 FDG-avidity and Malignant Shape of Cervical Lymph Nodes on PET/CT after Total Thyroidectomy Predict Resistance to High-dose I-131 Therapy in Patients with Papillary Thyroid Cancer - Byun, Byung Hyun (Asia Ocean J Nucl Med Biol, 2013)
OBJECTIVE: Resistance of metastatic lymph nodes (LNs) to high dose I-131 therapy is associated with high morbidity in patients with differentiated thyroid cancer. We evaluated the role of F-18 FDG PET/CT in the prediction of resistance to high dose I-131 therapy in patients with papillary thyroid cancer. METHODS: The subjects were 307 patients who underwent total or near total thyroidectomy followed by high dose (5.55-6.66 GBq) I-131 therapy. We divided the patients into three subgroups by visual assessment of regional LNs: FDG-avid LNs with a malignant shape on CT (PET/CT-positive group), FDG-avid LNs with a benign shape on CT (PET/CT-intermediate group) and no FDG-avid lesion (PET/CT-negative group). We measured the maximum SUV (SUVmax) of FDG-avid LNs in each patient. The presence or absence of focal increased uptake of I-131 was evaluated by whole body scan (WBS), and was denoted as WBS-positive group or WBS-negative group, respectively. Resistance to therapy was defined as presence of thyroglobulin (Tg) in serum (Tg ≥1.0 ng/ml) 3-6 months after I-131 therapy. Univariate and multivariate analyses were performed to determine the relationship between resistance to I-131 therapy and various clinico-pathologic variables. RESULTS: PET/CT-positive, intermediate, and negative groups included 20 (6.5%), 44 (14.3%) and 243 (79.2%) patients, respectively. The mean SUVmax was significantly higher in the PET/CT-positive group than that of the PET/CT-intermediate group (4.6 vs. 2.7, P <0.001). Univariate analysis revealed that the PET/CT-positive group (P <0.001), T2-4 stage (P <0.001), N1b stage (P = 0.001), lower dose (5.55 GBq) of I-131 (P <0.001), and the WBS-positive group (P = 0.029) were associated with resistance to therapy. In multivariate analysis, the PET/CT-positive group, lower dose of I-131, N1b stage, and T2-4 stage remained significant with odds ratios of 10.07 (P <0.001), 3.82 (P <0.001), 3.58 (P = 0.001), and 2.53 (P = 0.009), respectively. CONCLUSION: FDG-avidity and malignant shape of cervical LNs on pre-therapy FDG PET/CT were a strong risk factors predicting resistance to high dose I-131 therapy. A lower dose of administered I-131 (5.55 GBq) and more extensive tumors (T2-4 and N1b) were also associated with resistance to high dose I-131 therapy.